OPTIMIZATION FOR ALCOHOL FERMENTATION CONDITIONS OF SEA BUCKTHORN PRESS RESIDUES USING RESPONSE SURFACE METHODOLOGY - Anca-Mihaela GÂTLAN (Stefan cel Mare University of Suceava, 2019)
Sea buckthorn (Hippophae rhamnoides L.) is a unique and valuable shrub cultivated all over the world. Food industry is the most important sector of use of the sea buckthorn, where it is used as a raw material to obtain functional food or food supplements. Sea buckthorn fruits are among the most complex nutritionally of all berries. The aim of the present study was to offer an optimum solution for the valorization by alcoholic fermentation of the press residues obtained after processing the sea buckthorn fruit to obtain juice. The present research was conducted with the application of response surface methodology (RSM) for optimization, using a Box-Behnken design. The determined optimum conditions for a 3 days-fermentation were: a temperature of 25.38 °C, a pH of 4.62 and an inoculum size of 0.18 % to obtain a 3% vol. alc. beverage. This study provides useful information that can help beverage processing industries achieve optimum yield in low alcoholic beverage production using sea buckthorn press residues as sole substrate.